European Union : Publication of Financial Sector Assessment Program Documentation-Technical Note on European Securities and Markets Authority. (IMF Staff Country Reports; Country Report ;, 2013)
This article reviews the European Securities and Markets Authority (ESMA) of the European Union. ESMA performed a role in the regulation and supervision of the securities market. ESMA was created to supervise the financial system to enhance financial markets. In crisis management, ESMA focused on coordination, and identified and monitored risks. It also played an important role in the single rule book credit rating agency supervision. The assessment of the ESMA in the European Union is a next level in economic development.